PENGARUH KUALITAS PRODUK, HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN ES KRIM MEREK CAMPINA DI DKI JAKARTA - Bahari, Muhammad Cholid; Mirza, Mirza (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2020)
This Study Aims To Examine And Analyze The Effect Of Variable Quality Of Product, Price, And Brand Image On Purchase Decision Product Campina Ice Cream In Dki Jakarta. This Statistic Parametic Study Adopted Method That Use A Multiple Linear Regression In Which The Data Processed By Spss Vertion 21 Program. Sample Size Was 205 Consumers Who Tried And Buyed Ice Cream Campina As Respondents. The Instruments Used In The Form Of A Structured Questionnaire With Likert Scale Was Used To Collect Data Which Consisted Of 47 Questions Arranged Based On Indicator And Dimensions Derived From Each Variable. The Result Showed That Price, And Brand Image, Influencing The Purchasing Decision.